Pengaruh model Teaching Personal And Social Responsibility (TPSR) dengan menggunakan teknikal Hand Out olahraga kesehatan terhadap peningkatan tanggung jawab latihan dan aktivitas latihan fisik mahasiswa PGSD - Abdul Hakim (Universitas Sebelas Maret, 2025)
This study aimed to analyze the effect of the Teaching Personal and Social Responsibility (TPSR) model combined with a Health Sports Technical Hand Out (THO) on improving training responsibility and physical activity among Primary School Teacher Education (PGSD) students at IPI Garut. A quasi-experimental method with a pretest-posttest control group design was employed. The sample, selected purposively, consisted of two classes: an experimental group receiving the TPSR+THO intervention and a control group without treatment. Instruments included a training responsibility questionnaire and a physical activity observation sheet, both validated and tested for reliability. Data analysis used paired t-tests, gain scores, and independent sample t-tests (α = 0.05). Results showed significant improvements in all variables for the experimental group, with the largest gains in duration (+38.40 minutes; d = 1.142) and training intensity (+41.80 points; d = 2.447). These findings confirm that integrating TPSR and THO effectively fosters responsible character and enhances the quality of students’ physical activity. This model has strong potential for implementation in character-based physical education at the university level.